Red Palm Olein Oil-Enhanced Instant Noodle: A Functional Food Innovation for Diabetes-friendly Formulation - Budiyanto, Budiyanto; Silsia, Devi; Anis, Ulfah; Fatharani, Arina; Azima, Fauzan; Cahyana, Yana; Nizori, Addion (Indonesian Food Science and Technology Journal, 2026)
The global rise in type-2 diabetes has increased interest in functional foods that can help prevent or manage the disease. Red Palm Olein Oil (RPOO), rich in antioxidants such as tocotrienols, tocopherols, and β-carotene, has shown promise in reducing oxidative stress and improving insulin sensitivity. This study aimed to develop a low-calorie, functional instant noodle using RPOO to provide anti-diabetic benefits while retaining consumer appeal. Konjac flour, a low-calorie ingredient, was combined with RPOO to create a nutritious noodle product. The production of RPOO involved fractionating crude palm oil (CPO) to yield a product rich in antioxidants, which were measured for their antioxidant activity. The noodles were formulated by replacing conventional oils with RPOO-based seasoning, and their physical, chemical, and sensory properties were analyzed. Results showed that the RPOO-substituted noodles had significantly higher vitamin E content, contributing to antioxidant effects. Sensory evaluation indicated that the 75:25 RPOO-seasoning oil ratio received the highest acceptance regarding color, aroma, and taste. Proximate analysis revealed that the noodles were low in calories (73.81 kcal per 100g), making them suitable for health-conscious consumers. The findings suggest that RPOO-enhanced instant noodles could serve as a functional food for diabetes-friendly formulation, providing a novel approach to integrating health benefits into widely consumed food products.